Prevalence and clinical features of Paget's disease of bone in Japan. - Hashimoto, J; Ohno, I; Nakatsuka, K; Yoshimura, N; Takata, S; Zamma, M; Yabe, H; Abe, S; Terada, M; Yoh, K; Fukunaga, M; Cooper, C; et al. (2006)
The present study aimed to evaluate the prevalence and clinical presentation of Paget's disease of bone (PDB) in Japan. As PDB is a very rare disease in Japan, a nationwide mail survey was conducted targeting doctors in the specialty most frequently diagnosing and treating PDB patients in Japan. First, the literature for all case reports in Japan published between January 1990 and December 2002 was reviewed to determine who was diagnosing and treating PDB in Japan. This literature review for all case reports in Japan revealed that 72.1% of cases in Japan were reported from departments of orthopedic surgery. A nationwide two-phase mail survey was conducted for the departments of orthopedic surgery of 2,320 general hospitals accredited by the Japanese Orthopaedic Association. Phase 1 involved determining how many patients with PDB were followed at each hospital. If the answer was one or more, phase 2 of the survey gathered information on the clinical presentation of current patients. The mail survey yielded a final response rate of 75.4% for phase 1 and 87.6% for phase 2. Phase 1 indicated that the prevalence of PDB in Japan is about 2.8 cases per million capita. Phase 2 revealed a slight female predominance, lower frequency of familial clustering, higher frequency of femoral fracture in the affected femur, and a higher ratio of symptomatic PDB in Japan compared with findings in countries displaying a higher prevalence of PDB. The present epidemiological study revealed that the disorder is extremely rare in Japanese individuals, and that some differences exist with regard to the clinical features of PDB between Japanese patients and patients from high-prevalence countries.